Efficiency Improvement of Vertical Axis Wind Turbines with an Upstream Deflector. (August 2017) - Stout, Craig; Islam, Sheikh; White, Alasdair; Arnott, Scott; Kollovozi, Erald; Shaw, Morven; Droubi, Ghazi; Sinha, Yashwant; Bird, Benjamin
Abstract: The suitability of using an upstream deflector to improve the efficiency of a vertical axis wind turbine is presented in this study. A two-dimensional vertical axis wind turbine (VAWT) was modelled and simulated using ANSYS Fluent 14.0 computational fluid dynamics (CFD) software to solve the k-epsilon (RNG) turbulence model. Firstly, the open rotor design was optimised by varying orientation and pitch angle, prior to analysing the effect increasing wind speed had on the turbine performance. A maximum efficiency of 19.101% was achieved and was used as the open rotor design. A series of curved upstream deflectors were then evaluated in terms of efficiency improvements against the original open rotor design. Installation of the deflector resulted in a redirection of the fluid flow from the returning turbine blade, therefore reducing the negative torque induced on the system. Additionally, deflector width angles of 45 o and 36 o were found to improve the turbine performance by 1.266%. Finally, a scale model of the wind turbine was constructed and experimentally tested using a wind tunnel. No correlation between the CFD and experimental results was found due to variations in the wind speed tested by both methods. However, the VAWT design operated at a reasonably efficient level during the experimental testing, even under suboptimal conditions.